2009
DOI: 10.1002/ccd.22030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine and theophylline on coronary hyperemia induced by adenosine or dipyridamole

Abstract: For dipyridamole-stress myocardial perfusion studies, caffeine products and theophylline medications should be discontinued for 24 hr. For adenosine-stress myocardial perfusion studies, theophylline medications should be discontinued for 12 hr; however, one cup of coffee may be taken up to 1 hr before the test without necessitating a delay or cancellation of the study. These same considerations hold true for patients undergoing cardiac catheterization and intravenous adenosine-induced hyperemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…A number of studies have shown limited increase in myocardial blood induced by dipyridamole after caffeine use as well as attenuated myocardial perfusion defects. [53][54][55][56][57][58] Two studies assessing the coronary hyperemia induced by adenosine found no significant attenuation of the effect by caffeine. 56,59 It is unclear whether the degree of attenuation of the magnitude of coronary hyperemia caused by caffeine would result in a clinically significant change to myocardial perfusion results.…”
Section: Caffeine and Coronary Vasodilatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown limited increase in myocardial blood induced by dipyridamole after caffeine use as well as attenuated myocardial perfusion defects. [53][54][55][56][57][58] Two studies assessing the coronary hyperemia induced by adenosine found no significant attenuation of the effect by caffeine. 56,59 It is unclear whether the degree of attenuation of the magnitude of coronary hyperemia caused by caffeine would result in a clinically significant change to myocardial perfusion results.…”
Section: Caffeine and Coronary Vasodilatorsmentioning
confidence: 99%
“…[53][54][55][56][57][58] Two studies assessing the coronary hyperemia induced by adenosine found no significant attenuation of the effect by caffeine. 56,59 It is unclear whether the degree of attenuation of the magnitude of coronary hyperemia caused by caffeine would result in a clinically significant change to myocardial perfusion results. 60 A number of studies have investigated the effects of caffeine consumption on the MPI results using adenosine stress finding some effect on imaging, 61 but often no significant effect.…”
Section: Caffeine and Coronary Vasodilatorsmentioning
confidence: 99%
“…The advantage of the CT calcium score is the ease of incorporating a same‐day CAC test at the outpatient setting. Preparation for the test is minimal unlike other cardiovascular stress test which requires cessation of certain medications 21 or abstinence from caffeinated products 22 . It also does not require additional heart rate lowering agents 23 or blood tests to ensure adequate renal function.…”
Section: Discussionmentioning
confidence: 99%
“…These agents are coronary vasodilators and exert their action by stimulating increases in coronary blood flow within the myocardium to maximal or near-maximal levels (11,12). However, the increase in coronary blood flow due to pharmacologic stress does not translate into a linear increase in myocardial tracer concentration.…”
Section: Discussionmentioning
confidence: 99%